2019
DOI: 10.1159/000497445
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23 Trajectories in Chronic Hemodialysis Patients: Lessons from the HEMO Study

Abstract: Background: Long-term patterns of fibroblast growth factor 23 (FGF23) are poorly characterized among dialysis patients. Objectives: To identify different FGF23 trajectories and determine clinical factors that predict distinct FGF23 trajectories and whether FGF23 trajectories differ in regard to their associations with all-cause mortality among prevalent hemodialysis patients. Methods: The HEMO study was a randomized multicenter study evaluating the effects of high-dose vs. standard-dose and high-flux vs. low-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
(33 reference statements)
2
6
0
Order By: Relevance
“…[33][34][35][36] Of note, a recent ancillary study of the Chronic Renal Insufficiency Cohort (CRIC) study 44 demonstrated that individuals with rapidly rising FGF23 trajectories were at >15-fold higher risk of death than those with stable FGF23 levels. A similar pattern of association was reported from the HEMO study, 45 but the effect size was far smaller than that of the CRIC study. In aggregate, it appears that an association between elevated FGF23 and mortality could exist in prevalent hemodialysis patients, but to a lesser extent compared with the predialysis and incident hemodialysis populations.…”
Section: Discussionsupporting
confidence: 82%
“…[33][34][35][36] Of note, a recent ancillary study of the Chronic Renal Insufficiency Cohort (CRIC) study 44 demonstrated that individuals with rapidly rising FGF23 trajectories were at >15-fold higher risk of death than those with stable FGF23 levels. A similar pattern of association was reported from the HEMO study, 45 but the effect size was far smaller than that of the CRIC study. In aggregate, it appears that an association between elevated FGF23 and mortality could exist in prevalent hemodialysis patients, but to a lesser extent compared with the predialysis and incident hemodialysis populations.…”
Section: Discussionsupporting
confidence: 82%
“…Median iFGF23 was elevated at 1135 (interquartile range: 361, 3195) pg/ml, which is comparable to values observed in end-stage kidney disease cohorts 5 . The strongest association was between higher levels of iFGF23 and grades of diastolic dysfunction (r s = 0.75; P < 0.001), followed by serum phosphate and iFGF23 (r s = 0.51; P < 0.001).…”
Section: Resultssupporting
confidence: 59%
“…Both studies found, in different populations, that increasing FGF23 is disadvantageous. However, the study by Jovanovich in over 900 dialysis patients showed that, although over 24 month stable low FGF23 concentration was associated with a favourable outcome compared to stable high FGF23 concentrations, the group with high FGF23 in which FGF23 further increased over time, had no further increased risk for all-cause mortality [59]. More importantly, this study also showed that in patient with high baseline, and subsequently decreasing FGF23 concentrations had no improved risk for mortality.…”
Section: Is It Useful To Measure Serial Fgf23 Concentrations?mentioning
confidence: 53%
“…Future studies should evaluate whether multiple measurements of FGF23 may be advantageous compared to a single measurement for individual patients risk assessment in those with CKD, as it was shown that especially increasing FGF23 concentrations over time are associated with increased mortality [58,59].…”
Section: Fgf23 As a Risk Predictormentioning
confidence: 99%